Integration of the Indian Stock Market with Select Asian Stock Markets : An Analysis - Agrawal, Pravin Kumar; Nandan, Tanuj; Singh, Ashutosh Pratap (Indian Journal of Finance, 2021)
The present study explored the long-term associative relationships and the short-run causal relationships between stock market indices of select Asian economies: India, China, Hong Kong, Indonesia, Japan, Singapore, South Korea, and Taiwan. These countries make significant contributions in terms of foreign portfolio investments in India. The techniques of the Augmented Dickey – Fuller test, Phillips – Perron test, Granger causality test, and Johansen cointegration test were employed to trace the interdependence among the selected markets. Both Augmented Dickey – Fuller and Phillips – Perron tests revealed that all markets contained unit root at level and were integrated of order one. The results of the Granger causality test indicated a unidirectional relationship between Nifty50 and Indonesian and Japanese stock markets. Furthermore, it was found that bi-directional causal relationships existed between the stock markets of India and Hong Kong as also Singapore. The quarterly data of all the indices spanning the period from January 01, 2000 – March 31, 2018 were collected for the study. The cointegration test results revealed that international investors from China, Japan, Hong Kong, Singapore, and South Korea would not benefit from portfolio diversification to the Indian stock markets since a long-term equilibrium relationship existed between these markets.